POSITIVE FUNCTIONING FEATURES OF STUDENTS WITH DISABILITIES - Гуляєва, Олена Володимирівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2018)
In contemporary psychology positive functioning is virtually identifid with the concept of psychological well-being. According to eudemonistic approach in the structure of psychological well-being, personal potential, realization of which in different filds of life provides well-being and self-actualization can be marked out. Personal potential is the total resources of positive functioning, which reflct successful life creation. Self-actualization represents the effective process of living, realization of one’s own way and selfimplementation. The article is dedicated to analysis of personal sources of psychological well-being and selfactualization of students with disabilities as indices of their positive functioning. During empirical research it was established, that the level of positive functioning of such students is caused by the degree of realization of such components of personal source of psychological well-being as self-acceptance and the ability to manage complex environments, and moreover components of self-actualization – autosympathy and spontaneity. In addition, the ability to manage complex environments and spontaneity are specifi components, which determine the level of positive functioning of students with disabilities.